Variation of floral volatiles and fragrance reveals the phylogenetic relationship among nine wild tree peony species. (25th December 2019) - Luo, Xiaoning; Yuan, Meng; Li, Bingjie; Li, Chenyao; Zhang, Yanlong; Shi, Qianqian
Abstract: In recent years, more and more attention has been paid to the natural floral volatiles in tree peony and the fragrance components have been widely used in the fields of health care, perfumes, and cosmetics. However, there is little research on the identification of fragrance components of wild tree peony species. In present study, volatile components in petals of nine wild tree peony species were analyzed using a headspace solid‐phase microextraction (SPME) technique coupled with gas chromatography–mass spectrometry (GC‐MS). A total of 124 volatile components were identified and clustered into five major chemical classes: terpenoids, alkanes, alcohols, aldehydes, and ketones. Overall, combined with the sensory evaluation of nine wild tree peony species, Paeonia. ostii (P2) performed herbal and waxy attributes, mainly dominated by hexanal and pentadecane, respectively. P rockii (P1), P qiui (P3), P jishanensis (P4), and P decomposita (P5) all possessed sweet attribute, which was positively correlated with geraniol and citronellol. P delavayi (P9), P lutea (P7), P ludlowii (P8), and P potanini (P6) performed intense floral attribute dominated by linalool and trans‐linalool oxide. Moreover, the results of principal component analysis (PCA) and hierarchical clustering analysis (HCA) showed P decomposita (P5), P qiui (P3), P rockii (P1), P jishanensis (P4), and P ostii (P2) in the Subsect. Vagiatae were mixed to form one cluster while P lutea (P7), P delavayi (P9), P ludlowii (P8), and P potanini (P6) in the Subsect. Delavayanae formed the other cluster. In terms of geographical distribution, the two clusters are consistent with the distribution of wild tree peony species. The present study clarified the relationship between fragrance and components and further revealed the phylogenetic relationship of nine wild tree peony species, thus providing a theoretical basis for their development and utilization. Abstract : A total of 124 volatile components were in nine peony species. The results of PCA and HCA showed P decomposita, P qiui, P rockii, P jishanensis and P ostii in the Subsect. Vagiatae were mixed to form one cluster with P lutea, P delavayi, P ludlowii and P potanini in the Subsect. Delavayanae formed the other cluster, which was consistent with the distribution of wild tree peony species.